Role of DWI In Benign and Malignant Pelvic Pathologies in Female Keeping Histopathology as Gold Standard - Zubair, Hafsa; Asmat, Faryal; Farooq, Kiran Fatima; Wasim, Sairah (Indus Journal of Bioscience Research, 2025)
Objectives: evaluate the role of diffusion-weighted imaging (DWI) in benign and malignant pelvic pathologies in females keeping histopathology as the gold standard. Study Settings: Fauji Foundation Hospital, Rawalpindi, Punjab, Pakistan. Duration of Study: December 6, 2024 to June 6, 2025. Data Collection: A total of 448 female patients aged 18–65 years presenting for pelvic MRI were enrolled via non-probability consecutive sampling. After clinical evaluation, DWI was performed and results were compared to histopathology. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy were calculated. Subgroup analysis was done based on age, BMI, menopausal and marital status, and mass origin. Results: DWI demonstrated high diagnostic performance with a sensitivity of 98.23%, specificity of 88.36%, PPV of 74.00%, NPV of 99.33%, and overall accuracy of 90.85%. Subgroup analyses confirmed consistent performance across demographic and clinical variables, with sensitivity and NPV exceeding 97% and 98% respectively in all groups. Conclusion: DWI is a highly sensitive and non-invasive imaging modality that reliably differentiates between benign and malignant pelvic masses in women.